2009
DOI: 10.1590/s0001-37652009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular markers predictive of dengue hemorrhagic fever

Abstract: The management of acute dengue patients during outbreaks is a challenging problem. Most of the dengue fever cases are benign, but some cases develop into a severe and possibly lethal vasculopathy, known as dengue hemorrhagic fever. Early symptoms of dengue and hemorrhagic fever are very similar. An early differential diagnosis is needed to predict which of these two clinical presentations is crucial to proper patient care and public health management. This study evaluates the predictive potential of specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Coffey et al (2009) tested the extremely valuable identification of markers and candidate genes of dengue severity. Previously, we suggested that the measurement of several genes by qPCR in PBMC samples collected from dengue-infected patients during the acute phase of the disease could be useful for prognosis of DHF development (Calzavara-Silva et al 2009). Here, we reinforce the viability of using a panel of carefully selected genes to assess the likelihood of developing DHF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffey et al (2009) tested the extremely valuable identification of markers and candidate genes of dengue severity. Previously, we suggested that the measurement of several genes by qPCR in PBMC samples collected from dengue-infected patients during the acute phase of the disease could be useful for prognosis of DHF development (Calzavara-Silva et al 2009). Here, we reinforce the viability of using a panel of carefully selected genes to assess the likelihood of developing DHF.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work (Calzavara-Silva et al 2009), we suggested that it is possible to define genes that are differentially expressed between DF and DHF patients during the onset of symptoms and, consequently, predict the propensity of a dengue patient to progress to the severe form of the disease. Here, we propose the use of five genes that may predict a propensity of a DENV-infected patient to develop the severe symptoms of dengue as a molecular tool to aid DHF clinical diagnosis.…”
mentioning
confidence: 99%
“…In a patient who was infected with dengue, the markers could identify the evolution of the virus from the classical disease form to the hemorrhagic disease form. Despite the small sample (n = 16), these markers may be useful for the prognosis of the severe form of dengue and in a rapid assay with potential clinical use [43]. Moreover, among the studies that were included in this review, only Dos Santos et al, used the ELISA to capture the NS1 antigen in the acute phase of dengue [45].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis generally made after the patients have presented with severe dengue symptoms. So a prognosis test which helps to distinguish the patients who are more prone to develop the disease severity could be able to safeguard by providing better medical attention [3,6](http://www.cdc.gov/dengue/clinicalLab/). Earlier we have reported that various biochemical oxidant-antioxidant markers in the circulation of dengue infected study subjects [16,23].…”
Section: Introductionmentioning
confidence: 99%